Study of Tribological Behavior of Silicon Carbide Based Aluminum Metal Matrix Composites under Dry and Lubricated Environment - Kalyan Kumar Singh; Saurabh Singh; Anil Kumar Shrivastava (Advances in Materials Science and Engineering)
Friction and wear behavior of silicon carbide based aluminum metal matrix composite and aluminum matrix alloy have been studied for sliding speeds of 3.14 m/s and 3.77 m/s and load range from 10 N to 30 N under dry and lubricated environment, respectively. The experiments were performed on pin on disk tribometer (Make: DUCOM). The composite was fabricated by stir casting process and has several challenges like inferior bonds and interfacial reaction products which will deteriorate the mechanical and tribological properties. Therefore, addition of reactive metal like magnesium (Mg) should be done which will lead to reduced solidification shrinkage, lower tendency towards hot tearing, and faster process cycles. Results have revealed that the developed composites have lower coefficient of friction and wear rates when compared with aluminum matrix alloy under dry and lubricated environment. Experimental results show that under dry condition coefficient of friction of both the matrix alloy and the composite decreases with increase in load, whereas it increases with increase in sliding speeds; on the other hand wear rates of both aluminum matrix alloy and the composites increase with increase in load as well as with sliding speeds. FESEM of worn surfaces are also used to understand the wear mechanisms.